2017
DOI: 10.1159/000470849
|View full text |Cite
|
Sign up to set email alerts
|

Children with a Higher Activity of Carbonic Anhydrase VI in Saliva Are More Likely to Develop Dental Caries

Abstract: Objective: This study aimed to analyze the concentration and activity of carbonic anhydrase (CA) VI in the saliva of school children. We investigated the relationship among caries, CA VI concentration/activity, flow rate, pH, and buffering capacity. Materials and Methods: Seventy-four school children were divided into a caries-free group and a caries group. Clinical examinations were conducted by one examiner according to World Health Organization criteria + early caries lesions. Salivary flow rate, pH, and bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(55 citation statements)
references
References 26 publications
3
48
0
Order By: Relevance
“…These findings were confirmed in a recent longitudinal investigation carried out by Borghi et al [15]. In addition, our research group demonstrated a 4.88 times higher likelihood for caries development when saliva of this children exhibited a CA VI activity higher than 1.75 [19].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings were confirmed in a recent longitudinal investigation carried out by Borghi et al [15]. In addition, our research group demonstrated a 4.88 times higher likelihood for caries development when saliva of this children exhibited a CA VI activity higher than 1.75 [19].…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, it is proposed that CA VI in dental biofilm contributes to the neutralization of biofilm acid in the microenvironment of the tooth surface as a consequence of the buffering performed by salivary bicarbonate and, thus, may help to prevent dental caries [7,20]. Nevertheless, different from our recent work demonstrating the power of CA VI activity in saliva to predict caries development [19], we were not able to show the same ability of CA VI activity in biofilm. A possible explanation for this finding could be that data of CA VI in biofilm showed a higher variation as compared with CA VI activity in saliva even though an appropriated number of individuals was used as evidenced by the sample power calculation which showed a power of 0.80.…”
Section: Discussionmentioning
confidence: 87%
“…From a pragmatic point of view, the salivary concentration of CA VI seems to be lower in adults 14 and schoolchildren 15,16 having caries experience. Considering the role of CA VI‐catalyzed bicarbonate buffer as an important parameter of the individual's ability to control pH fluctuations, it, however, is plausible to suppose that CA VI enzymatic activity can provide a more meaningful perspective of dental caries susceptibility.…”
Section: Introductionmentioning
confidence: 96%
“…CA6 is therefore suggested to be an important enzyme in oral physiology and tooth tissues integrity, i.e., resistance to caries and dental erosion 6,10 . However, data are conflicting as both high and low concentrations and activities of CA6 have been associated with caries 4,11,12 .…”
Section: Introductionmentioning
confidence: 99%